New unique existence criteria for higher-order nonlinear singular fractional differential equations - Wang, Hui; Zhang, Lingling; Wang, Xiaoqiang (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, a nonlinear three-point boundary value problem of higher-order singular fractional differential equations is discussed. By applying the properties of Green function and some fixed point theorems for sum-type operator on cone, some new criteria on the existence and uniqueness of solutions are obtained. Moreover, two iterative sequences are given for uniformly approximating the positive solution, which are important for practical application. At last, we give two examples to illustrate the main results.